Latina Nagara style of Shikara of Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the eastern elevation of the Nilkantha Mahadev Temple. The central shrine is the best preserved of all shrines in the tri-kuta (triple-shrine) temple. The Latina nagara (mono-spired) variety of shikhara atop the central shrine of the Neelkanth Mahadev temple has been renovated.